PENINGKATAN PENGETAHUAN MASYARAKAT TERKAIT CARA PENGGUNAAN OBAT BEBAS DAN BEBAS TERBATAS DI KELURAHAN DUREN SAWIT - Dessy Adelia Pramesty; Honey Iskandar; Niko Prasetya; Felix Maloni Sitanggang (Jurnal Pengabdian IKIFA, 2023)
abuse. Whether it’s medicine that has been prescribed by a doctor because of illness, or medicine that people get on their own initiative. Mistakes in drug use can certainly have a fatal impact on consumers, especially when using over-the-counter and limited over-the counter drugs. The aim of this activity is to increase the knowledge of the people of the Duren Sawit Village area regarding the use of over-the-counter and limited over-the counter drugs. The method used is through counseling and administering pretest and posttest questionnaires. The results obtained were an increase in the average community knowledge score. The conclusion that can be drawn is that the outreach carried out is able to increase public knowledge.